(untitled) (Baghdad Science Journal, 2025)
Biological activity substances was investigated in watery extract of lentil which found to contain phenols, tannin, saponins and resins while, flavons, terpens and steroids were not exist in the extract details explained that 5%, 10% of lentil extract largly inhibited the growth of Psedumonas aeruginosa then Escherichia coli and Bacillus subtilis. The growth of both Staphylococcus aureus and Salmonella typhimurium were slightly affected by all extract concentration. Extracellular protease were screened in all bacterial species under study. Complete inhibition was achieved for extracellular protease while different percentage of protease inhibition were seen for intracellular proteases.